Armenia and Eu: Security Agenda as a Fresh Start for Engagement - Ani Grigoryan (CES Working Papers, 2016)
EU Eastern Partnership has gone through a number of difficulties and impediments since its establishment. In the case of Georgia and Moldova we have observed some progress, however in all other cases there is a certain setback. The political spectrum of Armenia was narrowed after September 3, 2013. In mid-January 2016 president Sargsyan held a meeting with EU ambassador in Armenia where he particularly mentioned that EU engagement is a top priority for Armenia (Armenpress, 2016) thus demonstrating that attitudes by both sides towards further engagement have undergone transformations. In the context of current geopolitical developments, the security sector could serve as a platform for Armenia and EU to foster collaboration. Thus, the main goal of the research paper is to seek avenues for approximation in the area of security and hence provide both parties with a deeper understanding of mutual objectives and visions.
Keywords: 330; Security; Eastern Partnership; Nagorno-Karabakh; CSDP; Conflict Resolution